Generality (‘Āmm) in the Legal Spectrum of Conventional Law and Sharī’ah versus Common Noun in English Grammar (A Comparative Jurisprudential and Linguistic Approach) - Dr. Lutfullah Saqib; Muhammad Amjad (Al Basirah, 2020)
Generality, indeed, is an essential character of every legal system; otherwise, they begin to lose, at ground level, their practicality and efficiency. Both Sharī‟ah and the conventional legal system, therefore, employ generality as a matter of jurisprudential principle, as it ensures „equality before law‟ and „justice for all‟ without any discrimination. Putting great belief in generality, legal experts, predominantly, those exercising authority in their corresponding jurisprudence, propose generality in the legal texts – leaving no space for any compromise under the umbrella of legal interpretation, both at textual and contextual levels. On the other hand, the Common Noun of English grammar, showing generality of meaning, corresponds with generality in English law and „āmm (general terms) in Sharī‟ah. Though, the two legal systems have included the general rules, nevertheless, the Islamic legal system uses the generic nature of words in a better way under a fine structure and mechanism. Apart from generality, both the systems identify certain restrictions (khāss) under specific conditions in order to deal a myriad of situations. The present work, primarily, aims at comparing the general rules, adopted by both the systems and, thus, at highlighting commonalities among them. It also intends to pinpoint the differences of their adaptation and application of the same rule. The findings, reached herein, show that both present similarities/commonalities and, of course, differences, albeit insignificant and unnoticeable. Sharī‟ah (Islamic law), however, is more superior in its approach and application of general words in its legal texts and contexts. Moreover, this work suggests new dimensions, as guidelines, for experts in the interpretations of their laws concerned. As the study is qualitative in nature, therefore, discourse analysis technique (narrowly can be called descriptive methodology), an appropriate method, herein, has been used for the investigation of the issue under probe.